Ray-density normalization for ray-optical wave propagation modeling in arbitrarily shaped tunnels. - Didascalou, D.
This work is concerned with the calculation of natural electromagnetic (EM) wave propagation and the determination of the propagation channel characteristics in highway or railway tunnels in the ultrahigh-frequency (UHF) range and above (>300 MHz). A novel ray-tracing technique based on geometrical optics (GO) is presented. Contrary to classical ray tracing, where the one ray representing a locally plane wave front is searched, the new method requires multiple representatives of each physical EM wave at a time. The contribution of each ray to the total field at the receiver is determined by the proposed ray-density normalization (RBN). This technique has the further advantage of overcoming one of the major disadvantages of GO, the failure at caustics. In contrast to existing techniques, the new approach does not use ray tubes or adaptive reception spheres. Consequently, it does not suffer their restrictions to planar geometries. Therefore, it allows one to predict the propagation of high-frequency EM waves in confined spaces with curved boundaries, like tunnels, with an adequate precision. The approach is verified theoretically with canonical examples and by various measurements at 120 GHz in scaled tunnel models
Keywords: 120 GHz; EHF; HF EM wave propagation; UHF range; Arbitrarily shaped tunnels; Curved boundaries; Electromagnetic wave propagation; Geometrical optics; High-frequency EM wave propagation; Highway; Image theory; Measurements; Mobile communications; Perfectly conducting corrugated circular waveguide; Plane wave front; Propagation channel characteristics; Railway tunnels; Ray-density normalization; Ray-optical wave propagation modeling; Ray-tracing technique; Receiver; Scaled tunnel models; Total field; Ultrahigh-frequency.